(untitled) (Journal of Parents and Teachers, 2016)
The following article deals with the emotional education. The empathy’s characteristics are the key to their social development. In addition, it considers the external influence in the emotional and cognitive person’s ability while he or she develops. Everything is essential in the educational context that it lives nowadays.